Program Pembangunan Desa di Provinsi Jambi, Sebelum dan Sesudah Menerima Bantuan Keuangan - Mardianis Mardianis; Susi Desmaryani (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2021)
The role of the Local Government in improving the people's economy is still very important and is the responsibility of the government in prospering the community. Provincial Government Funding to Villages (BKP2DK) in Jambi Province, is one of the sources of funds that contribute to the implementation of development in the village with the aim of improving the welfare of the community and reducing the number of poor ducking in the village / Kelurahaan. This research aims to see how the implementation of Jambi Provincial Government Funding to Villages in Jambi Province. The research method used is a quantitative descriptive method with sampling using purposife sampling method against village devices and rural communities in Jambi Province. While the analytical method used descriptive analysis by describing the conditions of the studied variables, and statistical analysis using gaps tests. The findings of this study show that the implementation of Provincial Government Funding in the field of infrastructure is more widely used for the development of BUMDES, while the field of institutional strengthening is more allocated to syara/guru ngaji officers. In this study it was also found that there is still a lack of coaching and supervision roles carried out by the Provincial and Regency/City Evaluation Teams so that there are some uses of financial assistance that have not been in accordance with the instructions that have been established. However, jambi province's funding was able to improve the welfare of the villagers judging by the dwindling number of poor people and the number of poor families, as well as the increasing number of Village Owned Enterprises (BUMDES) and Medium, Small and Micro Enterprises (MSMEs) in the village that sampled the research.